Carboxylic acid amide (CAA) fungicide resistance prevention strategy - Moore, M.S.; Follas, G.B.; Hagerty, G.C.; Beresford, R.M. (New Zealand Plant Protection, 2008)
CAA fungicides are currently represented in New Zealand by the three active ingredients dimethomorph iprovalicarb and mandipropamid They are currently registered in New Zealand for use against oomycete fungi in grapes onions potatoes and lettuce These fungicides are considered to have low to medium risk of resistance development and resistance management is recommended by the Fungicide Resistance Action Committee (FRAC) in Europe Guidelines are presented for fungicide use that will avoid or delay the development of resistance to CAA fungicides